Cold Atmospheric Pressure Gliding arc Plasma Jet for Decontamination - Tung, Do Hoang; Minh, Bach Sy; Thom, Vu Thi; Trang, Lam Thi Huyen; Huong, Cao Thi; Tuyen, Nguyen Thi (Communications in Physics, 2016)
A cold atmospheric pressure gliding arc plasma jet has been developed and applied to disinfection. The size of the plasma output is about 6 mm in diameter and 10 mm in length. Ar gas at a flow rate of 10 slm and 25 W plasma power are used. Plasma discharge is produced between the divergent electrodes and the jet appears as an effluence of the gas flow. When a pseudomonas culture is placed at 8 mm below the torch for 1minute, where the gas is at room temperature, the bacteria within a 16 mm diameter circle are almost completely killed. As the UV radiation is well below the safety regulation, the bacteria are inactivated by the total effect of UV radiation and others like the reactive species and the charged particles.